Parental awareness of young children's pattern of ionic beverage consumption. Issue 10 (21st October 2018) - Okumura, Akihisa; Ida, Shinobu; Ito, Setsuko; Oguni, Tatsuya; Suzuki, Mitsuyoshi; Mori, Masaaki; Shimizu, Toshiaki
Abstract: Background: The aim of this study was to investigate consumer perception of ionic beverage consumption by young children as a potential link to their excessive use. Methods: We studied parents' awareness of ionic beverages and the current pattern of use in their young children using a self‐administered questionnaire. Results: A total of 424 responses were recorded. Approximately 25–33% of parents believed that ionic beverages are good for health and rich in nutrients and vitamins, but, only 5.9% of the parents agreed with the statement that ionic beverages are safe to consume in large quantities. Regarding their use, 11 children (2.6%) were drinking ionic beverages every day or several times a week. The parents of these children were classified into the frequent use group. The rates at which parents agreed with statements that ionic beverages are good for health and rich in vitamins were higher in the frequent use group than in controls. Conclusion: Parental awareness of ionic beverages, and current consumption patterns in their young children are generally good. Having a positive opinion about the benefits of ionic beverages was associated with excessive consumption.